Actualization of genetic word structure in literary name (on the material of the satiric novel by Oleg Chornoguz «Papakha Applicants») (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article is focused on creating satirical effect by means of word-formative stylistic devices. This paper also investigates the process of prose intellectualization and related peculiarities of irony and sarcasm implementation. The author also studies the problem of motivating literary anthroponyms, using onomastic units as expressive means in the satirical text and searching non-verbal factors that determine the onomastic unit choice. Moreover peculiar attention is given to the specific word structure in poetic units that tend to foreground all the elements of their genetic word structure. This research proves that these features can be implemented both by using internal form in the context and any affix type segment.One of the main devices to produce stylistically marked units in the language of Oleg Chornoguz is a lexical semantic method of word formation, which actively manifests itself in the category system of proper names. All derivatives are interrelated in form and content. Their verbal performance in linguistic context depends on the author’s intention. This paper reveals uneven aesthetic significance of various anthroponyms in analyzed literary work. Among them onomastic units can be singled out as the most active expressive means. Disclosure of stylistic meaning of a proper name is provided by co-creativity of the writer, aimed to actualize a certain element according to the author’s intention and the reader’s skill to use available subtext based on his /her own experience, as well as background knowledge. Profound analysis is made on the basis of the nominative language system involving literature and history data.
Keywords: onomastic unit; poetic unit; literary name; motivation; word formation devices aimed to create comic effect